Career stage theory and turnover intent among correctional officers - Griffin, Marie L. (Criminal justice and behavior, 2014)
Prior research on correctional staff turnover intent and turnover generally assumes that staff are impacted by the workplace in a similar manner regardless of career stage. This study examined whether correctional officers (N = 2,621) with a Southwestern correctional agency differed in their level of turnover intent across different career stages, and whether the impact of work environment variables on turnover intent varied across career stages. Results indicated that turnover intent was lowest among staff with less than 1 year into their careers, and that the effects of work environment variables on turnover intent varied greatly across the 4 career stages. Commitment to the organization was the only work environment variable to be a significant predictor of intent to leave among four career stages, with a negative association in each of the four career groups.